Die Realität des Religiösen: zum Verhältnis von religiöser und wissenschaftlicher Weltansicht bei Johann Gottlieb Fichte - Hofmann, Matthias (Zeitschrift für Theologie und Philosophie, 2025)
Religious and scientifically oriented worldviews are often seen as divergent in modern times. From this point of view, it may be surprising to find that the pioneers of modern thinking also argued that a religious and a scientific view of the world are basically convergent. This thesis can be found in the late philosophy of religion of Johann Gottlieb Fichte (1762-1814). The present article reconstructs the interrelation between religion and science ("Wissenschaftslehre") in Fichte's lectures on the philosophy of religion Die Anweisung zum seeligen Leben / The way towards the blessed life (1806) in the horizon of the transcendental philosophical foundations of "reality", as already developed in Fichte's early Wissenschaftslehre / Science of knowledge (1794/95). The article concludes with subsequent considerations on the problem of a "scientific" theology.